AKTIVITAS ANTIBAKTERI ISOLAT KAPANG ENDOFIT DARI KULIT NANAS (Ananas comosus (L.) Meer) - Siti Hamidatul Aliyah; Musfirotun Musfirotun; Nur Antriana (JURNAL BIOSENSE, 2021)
Pineapple contains an enzyme called bromelain which is can be used as antiseptic of mouth, antibacterial, antifungal, and disinfectant. Endophytic mold is a microbe that forms colonies in healthy tissues of living organisms, generally, endophytic microbes do not cause harmful symptoms in the tissue of their host. This study aims to isolate the endophytic shell origin of pineapple peel that has acted as an antibacterial. A total of 3 endophytic capsules, Ac-I, Ac-II and Ac-III were isolated from pineapple skin using PDA media. The three isolates were purified and microscopic examinations were performed. Antibacterial testing was performed by fermentation to produce supernatant, then tested using disc method (Kirby-Bauer method) with Staphylococcus aureus and Escerichia coli test bacteria. The 3 isolates obtained only 1 isolate Ac-III isolates that have activity as antibacterial, with the inhibition zone diameter in bacterium Staphylococcus aureus 7.65 mm while in the bacterium Escerichia coli 6,9 mm.